Implementasi Nilai-Nilai Pendidikan Agama Islam Dalam Pengembangan Kehidupan Moderasi Beragama Siswa - Atika, Nur (Al-Miskawaih: Journal of Science Education, 2023)
This article discusses the application of Islamic Religious Education values in developing and strengthening students' religious moderation at State Vocational High School 2, Jambi City. This article comes from qualitative research with data collection techniques using observation, interviews and documentation. The research results show that the application of Islamic Religious Education values in this school is carried out through two channels, namely; first, intra-curricular Islamic Religious Education learning. In this path, each material from each element of the Koran, Hadith, Aqidah, Akhlak, Fiqh and SPI has religious moderation achievements that are appropriate to the context of the material. Second, the implementation of religious programs, where religious activities – both Muslim and non-Muslim – are carried out in an orderly manner. The Moderation values achieved include; moderate (tawassuth), fair (i'tidal), tolerance (tasamuh), deliberation (syura), improvement (islah), pioneer (qudwah), non-violence (al-la'unf). Artikel ini membahas penerapan nilai-nilai Pendidikan Agama Islam dalam pengembangan dan penguatan moderasi beragama siswa di Sekolah Menengah Kejuruan Atas Negeri 2 Kota Jambi. Artikel ini berasal dari penelitian kualitatif dengan teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa penerapan nilai-nilai Pendidikan Agama Islam di sekolah ini dilakukan melalui dua jalur yaitu; pertama, pembelajaran Pendidikan Agama Islam  intra kurikuler. Pada jalur ini tiap-tiap materi dari masing-masing elemen Alquran Hadits, Aqidah, Akhlak, Fiqih dan SPI memiliki capaian moderasi beragama yang sesuai dengan konteks materi . Kedua, pelaksanaan program keagamaan, di mana pada jalur ini kegiatan keagamaan – baik yang muslim dan non-muslim – dilaksanakan dengan tertib. Adapun nilai-nilai Moderasi yang tercapai antara lain; moderat (tawassuth), adil (i’tidal), toleransi (tasamuh), musyawarah (syura), perbaikan (islah), pelopor (qudwah), anti kekerasan (al-la’unf).